THORACIC EPIDURAL ABSCESS DUE TO COMMUNITY-ACQUIRED METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - Rao S, Raghavendra; Seshadri, Shubha; Rao N, Karthik; Patil, Navin; Avinash, A; Kunder, Sushil Kiran; Ahmed, Talha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT A spinal epidural abscess threatens the spinal cord or cauda equina by compression and also by vascular compromise. If left untreated, an expanding suppurative infection in the spinal epidural space can impinge on the spinal cord, producing sensory symptoms and signs, motor dysfunction, and ultimately paralysis, followed by death. Hence, early intervention undoubtedly improves the outcome. The authors report a case of a 27-year-old female patient, who presented with paraplegia, and was found to have thoracic epidural abscess due to community-acquired methicillin-resistant Staphylococcus aureus. Keywords: Spinal cord, Cauda equina, Infection, Laminectomy, Drainage.